2011
DOI: 10.4028/www.scientific.net/amr.399-401.1282
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Amphoteric Bagasse Hemicellulose on Heavy Metal Adsorption

Abstract: In this paper, ions i.e. Cu2+, Pb2+and Cd2+ were absorbed by the amphoteric bagasse hemicelluloses, and the influences of pH value, adsorption time and the initial concentration of metal ion have been studied. The results show that the optimal adsorption pH values for Cu2+, Pb2+ and Cd2+ are 6.5, 6.0 and 7.5, respectively. The adsorption capacity to ions Cu2+, Pb2+ and Cd2+ reaches the maximum values when the adsorption time is 180 min. Net adsorption to ions Cu2+, Pb2+ and Cd2+ increases with increasing the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Therefore, AX has great potential application in producing bioadsorbent for heavy metal ion removal. Wang et al (17,18) reported the applications of carboxyl hemicelluloses-based adsorbents in adsorption of metal ions. However, further improvement in the absorption capacity of metal ion is required by introduction of more ligands in hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AX has great potential application in producing bioadsorbent for heavy metal ion removal. Wang et al (17,18) reported the applications of carboxyl hemicelluloses-based adsorbents in adsorption of metal ions. However, further improvement in the absorption capacity of metal ion is required by introduction of more ligands in hemicelluloses.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum adsorption capacity of HPC for Cu was 56.4 mg/g. Lijun Wang et al[34] explored the adsorption of Cu, Pb and Cd by bagasse.convenient to obtain lignite in the mining area when treating AMD. The isothermal adsorption…”
mentioning
confidence: 99%